Cytokine Regulation In Pubertal Girls With Opsomenorrhea Across Different Body Mass Index Categories - T. M. Kamalov; D. A. Musakhodjaeva; Z. Sh. Azizova (Zien Journals, 2026)
Menstrual rhythm disturbances during puberty often reflect a combination of neuroendocrine immaturity and early forms of ovulatory dysfunction. In the context of abnormal body weight, inflammatory mechanisms may serve as an additional factor modulating reproductive regulation
Keywords: opsomenorrhea; puberty; menstrual cycle; obesity